Civic Engagement in Scandinavia Volunteering, Informal Help and Giving in Denmark, Norway and Sweden - Henriksen, Lars Skov.; Strømsnes, Kristin; Svedberg, Lars.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Since the 1990's, a number of studies have documented a remarkable high and stable amount of popular engagement in civic organizations in Denmark, Norway and Sweden. Often these countries have been considered deviant cases against the proliferating decline of social capital studies. However, despite great international interest in the Scandinavian region, the volume argues that the civil societies and the civic engagement of these countries remain poorly understood. Most interest in the Scandinavian welfare models addresses the balance between state and market, but under communicates the role played by civil society and popular engagement in associations and voluntary organizations. The contributions offer a coherent portrait of stability and change in formal and informal forms of civic engagement over the past 25 years as well as offering contextualized knowledge of the history and institutional design in which Scandinavian civil societies are embedded.
Chp. 1: Civic Engagement in Scandinavia. Introduction to the Volume -- Chp. 2: The Scandinavian Organizational Landscape. Extensive, Deviant and Important -- Chp. 3: Trends in Volunteering in Scandinavia -- Chp. 4: Patterns of informal helping in the Scandinavian welfare states -- Chp. 5: Donations in a high tax environment -- Chp. 6: New forms of civic participation - Implications of social media on civic participation and organization in Scandinavia -- Chp. 7: The role of gender in volunteering and other non-profit activities in Scandinavia -- Chp. 8: The societal role of volunteering - remarks on the moral logic of the Scandinavian volunteer sector.
Keywords: Sociology; Sociology